Non-state actors’ role in the EU forest policy making - Magnusson, Wilhelm (2014)
The purpose of this research is to identify how E-NGO and forest stakeholders, in the study referred to as non-state actors, have influenced the EU timber regulation; through participation and lobbyism towards the decision- makers (policy makers) at EU and national level, to achieve adjustments in the legislative text. The study also examines the relationships between the forest stakeholders, the E-NGOs and the EU-institutions, regarding communication, cooperation, informal and formal consultation where interviews were accomplished with decision-makers from the EU-institutions, forest stakeholders, E-NGOS and representatives from Swedish authorities that participated under the development of the EUTR during the period of 2008-2013. The participation and lobbying from non-state actors have most likely affected the outcome of the regulation, through alterations in the legislative text and through influencing the EU-institutions. Several factors that have affected the efficiency and timing of the influence have been identified through interviews as well as various approaches to influence the decision makers. The findings of the study may be useful for forest related interest groups that are involved in decision-making procedures at EU-level and as substance and material for further research in the subject of forest policy making at supranational level.